“Macron’s Islamophobia Leads Boycott”: An Appraisal Analysis on Aljazeera News - Ratu Sarah Pujasari (English Language and Literature, 2021)
This article explores a selection news on Aljazeera online website about the issue of sweeping boycott on France Goods. This problem caused by the statement of France Macron as the President of French sprinkling the Islamophobia by his own statements. It was raising Muslim’s anger around the world. Based on the issues, this study will analyse about the issue and guided by the analytic framework of Appraisal, which is concern on an engagement analysis. The study reveals that heteroglossic occurred from the writer and the researcher found that the writer has a tendency to indulgence which showed dialogic contraction on the issue mentioned belong to disclaim and proclaims the propositions.